Avaliação da cinética de biodegradação dos compostos tóxicos: benzeno, tolueno, etilbenzeno, xileno (BTEX) e fenol - Trigueros, Daniela Estelita Goes (2008)
The aromatics hydrocarbons usually known as BTEX (benzene, toluene, ethylbenzene, and xylenes isomers) are toxics compounds presented in many petroleum products, such as gasoline, and are also widely used in chemical and petrochemical industries. When these compounds are released in the environment a contamination of the soil and the groundwater took place. As a result, the use of the aquifers becomes impossible. Groundwaters nowadays represent an alternative potable water source in many countries. Therefore, it s crucially important to study the biodegradation process, in particular when multiple substrates are presented in the system. In this work, the kinetics of BTEX biodegradation was studied, individually and as in mixture. Hence, the performance of the different microbial growth unstructured models, based on the population level kinetics were investigated by using experimental data from literature. The equations of the material balances, for batch operation mode, were numerically solved (RKF45 method) applying the Monod and Andrews models to describe an individual substrates biodegradation kinetics. Similarly, the applied equations describing mixture substrates biodegradation kinetics were solved by using the competitive, noncompetitive and uncompetitive inhibitions models as well as the sum kinetic interactions parameters (SKIP) model. Moreover, in order to understand the mechanisms involved in the biodegradation process of the BTP toxics compounds (benzene, toluene, and phenol), individually and as the binary and ternary mixtures, were investigated. In this case, some inhibition models modifications were proposed in order to describe the biodegradation kinetics of the benzene-toluene and benzene-phenol mixtures. The kinetic parameters were estimated by using Particle Swarm global optimization method. The experimental data were taken from the literature and the programs were coded in Maple software. The least square method was used as a statistical criterion of the search. The evaluated kinetic parameters values obtained in the present study were found to describe very well experimental data and to be in accordance with the values reported in the literature. The simple Monod and Andrews models accurately predict the BTEX individual biodegradation kinetics. The SKIP model provided the best description of BTEX biodegradation kinetics, showing the existence of non specific interactions between the BTEX substrates. The other models behavior indicated a presence of a competitive and a noncompetitive inhibition in the mixtures, agreeing with the reality that a mixture culture used in the biodegradation can have multiples metabolic pathways to the BTEX biodegradation. By applying the SKIP model, the interactions between BTEX substrates was estimated, where the ethylbenzene expressed a higher inhibitory effect in the mixtures, whereas the xylene shown a smaller one. The competitive inhibition model adequately described the BTP binary and ternary mixtures biodegradation process, because substrates biodegradation is catabolized via the same enzymatic pathway of Pseudomonas putida F1. Moreover, the inhibition models modifications proposed described better the biodegradation kinetics of benzene-toluene and benzene-phenol mixtures. Finally, the obtained results in this work have shown that the best models can be successfully applied for optimization of toxics compounds biodegradation process by applying different bioreactors types and operational conditions.